SELMA mission: How do airless bodies interact with space environment? The Moon as an accessible laboratory. (July 2018) - Futaana, Yoshifumi; Barabash, Stas; Wieser, Martin; Wurz, Peter; Hurley, Dana; Horányi, Mihaly; Mall, Urs; Andre, Nicolas; Ivchenko, Nickolay; Oberst, Jürgen; Retherford, Kurt; Coates, Andrew; et al.
Abstract: The Moon is an archetypal atmosphere-less celestial body in the Solar System. For such bodies, the environments are characterized by complex interaction among the space plasma, tenuous neutral gas, dust and the outermost layer of the surface. Here we propose the SELMA mission (Surface, Environment, and Lunar Magnetic Anomalies) to study how airless bodies interact with space environment. SELMA uses a unique combination of remote sensing via ultraviolet and infrared wavelengths, and energetic neutral atom imaging, as well as in situ measurements of exospheric gas, plasma, and dust at the Moon. After observations in a lunar orbit for one year, SELMA will conduct an impact experiment to investigate volatile content in the soil of the permanently shadowed area of the Shackleton crater. SELMA also carries an impact probe to sound the Reiner-Gamma mini-magnetosphere and its interaction with the lunar regolith from the SELMA orbit down to the surface. SELMA was proposed to the European Space Agency as a medium-class mission (M5) in October 2016. Research on the SELMA scientific themes is of importance for fundamental planetary sciences and for our general understanding of how the Solar System works. In addition, SELMA outcomes will contribute to future lunar explorations through qualitative characterization of the lunar environment and, in particular, investigation of the presence of water in the lunar soil, as a valuable resource to harvest from the lunar regolith. Highlights: We propose SELMA mission to study how airless bodies interact with space environment. SELMA uses a unique combination of remote sensing and in situ measurements at Moon. SELMA investigates the interaction between the plasma, gas, dust and surface at Moon. SELMA conducts two impact campaign measurements to study the environment. SELMA aims to launch in 2029 as a medium class mission of ESA's Cosmic Vision program.